DEZVOLTAREA TURISMULUI DURABIL ÎN JUDEŢUL SIBIU (PANGEEA, 2025)
Sustainable development of tourism in Sibiu County. The central idea underlying sustainable development is the preservation of biodiversity and cultural heritage for future generations. Lester Brown rightly states that: “we do not inherit the earth from our parents but we borrow it from our children”.